Study on the Behavior of Particles in High Reynolds Number in Semi Ellipse Lid Driven Cavity - Mohd Hafizi, Mohammad Yusoff; N. M. M., Ammar; Idris, Mat Sahat (2015)
This study is focusing on the behavior of fluid,flow and particle flow. The boundary of the study is concentrated more the behavior of particle flow inside semi ellipse shape lid driven cavity (benchmark for shallow cavity) using Stream function-Vorticity approach Navier-Stokes equation and validation of flow based on experiment analysis of particle flow in semi ellipse shear cavity. The height to length aspect ratios of 1:2 semi ellipse cavity were simulated using flow conditions (range of Reynolds numbers of 100 to 2500). The initial condition of the particle remains at rest at bottom wall of the lid driven cavity. The results obtain for semi ellipse lid driven cavity illustrate that the silk particle rotates in a swirling motion in the lid driven cavities and correlates with the computational method calculated.